Improving Science Learning Outcomes at SMP 02 Rumbia Through Model Problem Based Learning (PBL) - Majenun Majenun (Journal of Teaching and Education, 2022)
This research is a classroom action research (CAR), which aims to improve the science learning outcomes of class IX students of SMPN 02 Rumbia through the Problem Based Learning (PBL) model on electrical material in human and animal nerve cells that are capable of generating electricity. Data collection was carried out using learning outcomes tests and observations. The data collected were analyzed by descriptive analysis. From the results of data analysis, the average learning outcomes of the first cycle was 74.2. In cycles II and III, the average learning outcomes were 78.3 and 85.0. From the results of this study, it can be concluded that the PBL model is able to improve science learning outcomes.